2‐Hexadecenal inhibits growth of C6 glioma cells. (30th April 2019) - Amaegberi, Nadezda V.; Semenkova, Galina N.; Kvacheva, Zinaida B.; Lisovskaya, Alexandra G.; Pinchuk, Serge V.; Shadyro, Oleg I.
Abstract : 2‐Hexadecenal (2HD) formation in the organism occurs via irreversible enzymatic degradation of sphingosine‐1‐phosphate or nonenzymatic γ‐, UV‐, or HOCl‐induced destruction of a number of sphingolipids including S1P. The current research focuses on the study of 2HD effects on C6 glioma cells growth. The results obtained show that 2HD causes a dose‐dependent decrease in proliferative and mitotic indices. The change in the mitotic index is due to the redistribution of cells in the different phases of mitosis. These processes are accompanied by cytoskeleton rearrangement and changes in cell morphology, which are expressed in F‐actin redistribution, change in the number and type of filopodia and fibrils, leading to cell shape changes, decrease in intercellular contacts and monolayer rarefaction. Cells treatment with 2HD leads to apoptosis induction and signalling pathways modification, including activation of JNK, p38, and ERK1/2 MAPK but not PI3K. The effects observed are not related to the cytotoxicity of 2HD. Significance of the study: 2HD—an unsaturated aldehyde, which level can rise under conditions of oxidative stress as a result of nonenzymatic sphingolipids' destruction. The mechanisms of 2HD action on various cell types have not been sufficiently studied. Therefore, the study on functional role of this aldehyde in different cell types that may be its target is relevant. This study demonstrated that 2HD inhibits growth of C6 glioma cells due to modification of intracellular processes of signal transduction, cytoskeleton rearrangement, change in the mitotic regimen and apoptosis induction.